O ensino dos conceitos de área e perímetro através da resolução de problemas - Costa, Thelma Regina Vitor da [UNESP] (Universidade Estadual Paulista (Unesp), 2010)
When I set out to attend degree in mathematics was because I believed that mathematics could be taught to students in a way closer to their daily lives, thereby making it a more attractive school discipline, gradually, eliminating its reputation of a difficult school subject. Then, during my observations in supervised, I realized that one of the greatest difficulties in mathematics was related with geometry, in which the concepts of area and perimeter were often confused. Using the methodological tool of problem solving, something to bring the concept to be developed and the cultural context in which the student is in, I developed some educational activities in which, using concrete materials, students were encouraged to construct their own knowledge about the concepts of area and perimeter. Moreover, such activities were designed to place the student as the center of attention in the classroom. The main objective of this work is to encourage and observe how this methodology, based on the solving problem process, can be used within the classroom, to better understand the concepts to be taught, always looking for improvement of the student learning

Utilizando da ferramenta metodológica de resolução de problemas, algo para aproximar o conceito a ser desenvolvido e o contexto cultural no qual o aluno está inserido, desenvolvendo algumas atividades didáticas nas quais, por meio de material concreto, o aluno fosse incentivado a construir o seu próprio conhecimento dos conceitos de área e perímetro. Além disso, tais atividades foram elaboradas de forma a colocar o aluno como sendo o centro das atenções da sala de aula. O objetivo central deste trabalho é o de incentivar e observar como essa metodologia, baseada na Resolução de Problema, pode ser usada dentro de sala de aula, visando a uma melhor compreensão dos conceitos que serão ensinados, sempre na busca da melhoria do aprendizado do aluno. Os resultados mostram que ao utilizar essa metodologia de Resolução de Problemas e a Etnomatemática houve um maior interesse por parte dos alunos abrangidos na pesquisa, pois com o trabalho sendo prático ocorre um envolvimento dos alunos nas atividades
Keywords: Matemática - Estudo e ensino; Didática